IMF Research Bulletin, March 2010. (IMF Research Bulletin; IMF Research Bulletin ;, 2010)
This paper provides a brief overview of the latest research on the ability of forecasters to predict recessions. The paper highlights that few recessions have been forecast before their onset. Forecasters tend to be excessively cautious and do not revise their forecasts promptly and sufficiently to reflect incoming news. Nor do they fully take into account interdependence among economies. This paper also focuses on robust growth determinants highlighting that a fundamental problem confronting researchers is the lack of an explicit theory identifying the determinants of growth.